Penerapan Strategi UMKM Melalui Digitalisasi Promosi Untuk Meningkatkan Penjualan Produk UMKM Di Wonosobo - Eni Candra Nurhayati; Rahma Izzati (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
This research aims to evaluate the impact of Micro, Small, and Medium Enterprises (MSMEs) focused on food production in the village of Adiwarno, Selomerto District, Wonosobo Regency. These MSMEs have been operating for over 20 years in Wonosobo Regency, but still employ limited and conventional marketing methods. Therefore, these MSMEs require a workshop on the benefits of digital marketing to enhance their marketing system. The goal is to expand the reach of the business target and increase sales. Additionally, MSMEs are provided assistance in creating business accounts on social media platforms such as Facebook and Instagram, along with guidelines for optimization. The outcomes of this research include the creation of Facebook and Instagram business accounts, scholarly research published in national journals, and an activity report. The applied method involves workshops in the form of lectures and practical guisertace on creating and managing accounts in digital media. Based on the findings of this activity, it is recommended to continue the use of digital marketing strategies with periodic guisertace to maintain the effectiveness and optimization of strategies in supporting marketing activities and increasing sales for MSMEs.